Strategy of Implementation Highest Medium Rice Retail Price Policy - Rifai, Riyan Nur (Efficient: Indonesian Journal of Development Economics, 2020)
The purpose of this study is to find out what factors influence the implementation of the policy and formulate the strategy for implementing the policy. The main data type is primary data and is equipped with secondary data. Data collection methods are used interviews, questionnaires and literature studies. Research analysis used a SWOT analysis tool. Based on the results of the study that internal factors and external factors that influence the strength of internal factors consisting of easily published policies, adequate human resources, policy objectives and clear sanctions for policy violators. The weakness side is that the level of supervision is not optimal, the implementer rejects the policy, the highest retail price level is not right and the policy information has not been clearly conveyed. Whereas the opportunity side of external factors is the ability to increase rice stocks with imports, the government's readiness to fill rice stocks in the market and the public's encouragement to maintain stability in rice price stability. The threat side is the availability of rice from limited farmers, disruption of rice production factors and a long rice distribution chain. The right strategy used today is a defensive strategy. Tujuan penelitian ini untuk mengetahui faktor-faktor apa saja yang mempengaruhi implementasi kebijakan tersebut dan merumuskan strategi implementasi kebijakan tersebut. Jenis data utama digunakan data primer dan dilengkapi data sekunder. Metode pengambilan data digunakan wawancara, kuisioner dan studi kepustakaan. Analisis penelitian digunakan alat analisis SWOT. Berdasarkan hasil penelitian bahwa faktor internal dan faktor eksternal yang mempengaruhi yaitu dari sisi kekuatan pada faktor internal terdiri dari kebijakan mudah dipublikasikan, sumber daya manusia memadai, tujuan kebijakan dan sanksi jelas bagi pelanggar kebijakan. Sisi kelemahan yaitu tingkat pengawasan belum optimal, pelaksana menolak kebijakan, tingkat harga eceran tertinggi belum tepat dan informasi kebijakan belum tersampaikan dengan jelas. Sedangkan sisi peluang dari faktor eksternal yaitu kemampuan menambah persediaan beras dengan impor, kesiapan pemerintah untuk mengisi persediaan beras di pasar dan dorongan masyarakat untuk menjaga stabilitas stabilitas harga beras. Sisi ancaman yaitu ketersediaan beras dari petani terbatas, gangguan faktor produksi beras dan rantai distribusi beras panjang. Strategi yang tepat digunakan saat ini yaitu strategi defensif.